A systematic review and meta-analysis of randomized controlled trials, juxtaposing the control of glycemia and blood pressure between large dose empagliflozin and placebo among type 1 diabetes patients - Saha, Sumanta; Saha, Sujata (International Journal of Health Sciences, 2020)
Objectives: While empagliflozin (25 mg) is used to treat type-2 diabetes mellitus patients with optimum renal functioning, its efficacy and safety in type-1 diabetes mellitus (T1DM) is not yet established. Therefore, this study aimed to compare insulin-treated T1DM patients’ (with adequate renal functioning) glycemic and blood pressure control between the 25 mg empagliflozin recipients and placebo recipients. Methods: Parallel-arm randomized controlled trials comparing the effect of daily administered 25 mg empagliflozin tablets in adjunct to insulin treatment with placebo and insulin treatment in T1DM patients with an estimated glomerular filtration rate of 45 mL/min/1.73 m2 or more were eligible for inclusion. Trials were searched in PubMed, EMBASE, SCOPUS, and CENTRAL with no restriction on date and language. Risk of bias of trials was assessed and mean and standard deviation of glycated hemoglobin (HbA1c, in %), systolic blood pressure (mmHg), and diastolic blood pressure (mmHg) at the end of the trial period were collected, and random-effects meta-analysis was done to estimate the weighted mean difference (WMD). The metaanalysis was done in Stata statistical software. This study was conducted in June 2019. Results: Three relatively small-sized trials published between 2015 and 2018 were eligible for review and analyses. The trials suffered from unclear risk of performance and detection bias. The HbA1c reduction favored the intervention group (WMD = −0.478, 95% confidence intervals = −0.766–−0.189, P = 0.001; I2 = 0%). The WMD of blood pressure (systolic and diastolic) did not vary between the treatment groups. Conclusion: Evidence (of moderate quality) suggests that daily administration of empagliflozin 25 mg tablets in adjunct to insulin in T1DM patients with optimum kidney functioning is useful to achieve glycemic control compared to placebo and insulin therapy. However, the effect on blood pressure remained indistinguishable between the compared interventions.